Keabsahan Perjanjian Pra Nikah dan Akibat Hukumnya Ditinjau dari Perspektif Hukum - Sugih Ayu Pratitis; Rehulina Rehulina (Pusat Riset dan Inovasi Nasional, 2023)
. A marriage is an agreement based on personal voluntary agreement between a man and a woman to become husband and wife. In Indonesia, the contract or agreement is called a marriage contract (nuptial agreement or marriage). Pre-nuptial agreement is an agreement made by the prospective bride and groom before the marriage takes place so that it becomes a legal couple. Properly the contract The prenuptial agreement is also binding on both the bride and groom and contains issues of dividing the assets of the two parties or relating to the personal assets of both parties so that they can be separated, if one day there is a separation. An agreement is an event where a person promises to another person or where two people promise each other to do something. When compared to an engagement with an agreement, apart from the agreement being a source of engagement other than the law, the engagement is also an understanding that is still abstract, because the parties are said to carry out something, while the agreement is already a concrete understanding, because the parties are said to carry out something certain events. This research is a type of legal research that uses a normative juridical approach. The implementation of the marriage agreement so that the agreement is valid in the eyes of the law, the agreement must be made authentically before a notary. The prenuptial agreement is made for the benefit of legal protection of each other's innate assets, namely the property of the prospective husband or the property of the prospective wife. By making a Pre-Marriage Agreement, it will provide a sense of security to the prospective husband and wife in carrying out their household ark. Prenuptial agreements are made to confirm assets, rights of husband/wife, obligations of husband/wife and responsibilities of each party.